Influence of hypercholesterolemia on deformability and shape parameters of erythrocytes in hyperglycemic subjects - Babu, N. (Clinical hemorheology and microcirculation, 2009)
The main objective of the present work is to study the influence of cholesterol in hyperglycemic subjects on deformability and shape parameters of erythrocytes. The deformability of erythrocytes in blood samples of diabetic patients with normal cholesterol (group A) and diabetes with hyper cholesterol (group B) concentration are determined by optical hemorheometer and are compared with healthy subjects. The deformability is measured by passing laser light through erythrocyte suspension in physiological saline while filtration of erythrocytes through cellulose micro pore membrane. Blood samples of 5% hematocrit were prepared in physiological saline for control subjects and diabetes mellitus with normal and hyper cholesterol subjects for deformability measurements. The shape analysis is carried out by shape descriptors based on projected area, perimeter and form factor, as measured by processing of images of erythrocytes. Deformability was reduced in diabetes with normal cholesterol and much reduced significantly in diabetes with hyper cholesterol comparing to healthy subjects was found. The shape descriptor form factor, as determined by processing of erythrocyte images, increases in diabetes with normal cholesterol and further increases in diabetes with hyper cholesterol compare to healthy subjects and shows a pattern similar to filtration time of erythrocyte suspensions through cellulose membranes. This significant decrease in deformability and increase in shape parameters in diabetes with hyper cholesterol may increase the microcirculatory complications compare to diabetes with normal cholesterol.